STRATEGI INDUSTRI MUSIK BERTAHAN DITENGAH PANDEMI (TRINITY OPTIMA PRODUCTION) - nugroho adi (MediaKom : Jurnal Ilmiah Komunikasi, 2020)
The development of new media is part of the development of the internet. Many new media have emerged that make us have to adapt or be eroded by technological developments. Very sophisticated developments make changes to human life itself. New media is a term that describes the emergence of an era in communicating on the internet and YouTube is one of the most popular and widely used examples of new media today. During a pandemic with changes in communication patterns, a lot of work has to be done by utilizing new media, including YouTube.